Object following Robot using Computer Vision - Al-Mazeedi, Bader (2021)
This paper introduces a vision based object tracking robot which is driven by wheels and controlled by a raspberry pi that runs a dedicated software for image processing. The objective of this project is to design a robot which is automatically controlled by on board raspberry pi to track and follow a colored object. Robot will analyses the video stream to detect the colored ball, then using video array it will specify the location of the ball inside the video frame and depending on the current position the raspberry pi will decide to rotate right or left or to go forward until reaching the object. Set of software and packages are used to do this task, for the raspberry pi the operating system is Raspian with installed package of open CV, also hardware is required to accomplish this mission like the motors and the motors driver and the power supply.at the end the robot will automatically detect the object and move toward it until reaching it then stop.